Case 25-2019: A 41-Year-Old Pregnant Woman With Abdominal Pain. Issue 1 (March 2020) - Saillant, N.N.; Kilcoyne, A.; Fagenholz, P.J.; Lui, R.; Krystel-Whittemore, M.
Abstract : ( N Engl J Med . 2019;381(7):656–664) A 41-year-old women presented to the emergency room at 36 weeks and 3 days of gestation, complaining of abdominal pain. The pain was in the right lower quadrant and described as sharp and constant. She rated the pain at 8 on a 0 to 10 scale, with 10 indicating the most severe pain. The patient had had 4 previous pregnancies—2 were uncomplicated vaginal deliveries and 1 ended in spontaneous abortion. For her current pregnancy, her initial prenatal visit was normal and prenatal follow-up had been uneventful. Her obstetrician referred her to the clinic, where a transabdominal and transvaginal ultrasonography indicated no abnormal fetal findings. The patient was referred to another hospital's emergency department.